2020
DOI: 10.1186/s11671-020-3274-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Nano-Copper Sulfide and Its Adsorption Properties for 17α-Ethynyl Estradiol

Abstract: In the present work, a tubular nano-copper sulfide was successfully synthesized by hydrothermal method. The physical and chemical properties of the prepared materials were characterized by XRD, SEM, TEM, and BET. The synthesized copper sulfide was used as an adsorbent for removing 17α-ethynyl estradiol (EE2) and exhibited excellent adsorption properties. At 25°C, 15 mg of adsorbent was applied for 50 mL of 5 mg/L EE2 solution, adsorption equilibrium was reached after 180 min, and the adsorption rate reached ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…All the diffraction peaks can be assigned to the pure covellite hexagonal phase (JCPDS 06-0464). It can be observed that CuS QDs have well-defined characteristic diffraction peaks with 2θ values of (27.7°, 29.3°, 31.76°, 32.7°, 47.8°, 52.3°, 59.2°) which are corresponding respectively to (100), (101), (103), (006), (107), (108), and (116) crystal planes of the preferential orientation of CuS NPs 41 , 42 . CuS QDs have relatively high crystallinity and the most intense peak at 2θ = 31.76 relates to (103) diffraction plane.…”
Section: Resultsmentioning
confidence: 99%
“…All the diffraction peaks can be assigned to the pure covellite hexagonal phase (JCPDS 06-0464). It can be observed that CuS QDs have well-defined characteristic diffraction peaks with 2θ values of (27.7°, 29.3°, 31.76°, 32.7°, 47.8°, 52.3°, 59.2°) which are corresponding respectively to (100), (101), (103), (006), (107), (108), and (116) crystal planes of the preferential orientation of CuS NPs 41 , 42 . CuS QDs have relatively high crystallinity and the most intense peak at 2θ = 31.76 relates to (103) diffraction plane.…”
Section: Resultsmentioning
confidence: 99%
“…The intermediate product (Fe 2 S 3 ) is unstable and rapidly converts into FeS and S. The strong coordination between Fe and S results in the breakage of other metal bonds (e.g., of metal–linker) and ultimately results in the release of the linker and MOFs’ decomposition. The emergence of extra peaks at 28°, 32°, and 45–47° (2θ) in the PXRD pattern (Figure C) of the NaHS-immersed samples indicates the presence of a metal–sulfide linkage and correlates to the decomposition phenomenon. We also compared the FT-IR analysis of the NaHS immersed samples with non-NaHS-exposed samples and a free linker.…”
Section: Resultsmentioning
confidence: 99%
“…and As-adsorbed Fe/AlO(OH) showed type IV adsorption isotherm behavior. Moreover, Figure 7 showed H3-type hysteresis loops according to BDDT classification, indicating the samples contain meso-pores (2-50 nm) and will therefore enable high permeability of the contaminated water hence increasing the rate at which contaminants are scavenged out of the solution [51,55,56]. The nitrogen adsorption-desorption curve closely resembles that reported by Zhang et al [56] which was also interpreted as conforming to H3-type hysteresis with similar surface area and pore size as that measured in this study.…”
Section: Surface Area and Porosity Of Fe/alo(oh) Pre-and Post As-adso...mentioning
confidence: 99%